Evaluation of different safety aspects of centerline rumble strips - VijayaKumar, Arun (Kansas State University, 2009)
In this thesis, various safety aspects of center line rumble strips were evaluated. Based on the literature review center line rumble strips (CLRS) are considered to be effective safety countermeasure for reducing crossover accidents on two-lane, two-way roadways. CLRS are indentations milled into the center line of undivided two-lane, two-way roadways to warn driver of drifting into upcoming traffic. Researchers at Kansas State University (KSU) have conducted studies on CLRS and retroreflective pavement markings (RRPM) installed over them. Based on the literature review and the survey conducted on motorcycle riders it can be concluded that majority of riders believe in the effectiveness of CLRS and they recommend the KDOT to implement CLRS in more locations. From the survey conducted on residents of US 40 it can be concluded that RRPM help them in providing visual guidance. They also noticed that there is considerable deterioration of RRPM over CLRS on US 40. From the studies conducted on US 24, US 50 and US 40 it can be concluded that wet retroreflectivity of pavement markings installed over CLRS is considerably lower than dry retroreflectivity. In locations without CLRS wet retroreflectivity of RRPM is higher than dry retroreflectivity. Also, the analysis performed on retroreflectivity measurements from US 24, US 50 and US 40 show that retroreflectivity follows a linear reduction in performance over time. In addition, a new methodology was developed for evaluating RRPM over CLRS. Various tests and analysis were performed and the new method seems effective.
Keywords: Center line rumble strips; CLRS; Engineering, Industrial (0546)